Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

enter image description here

could anyone tell me how to calculate these sums?I am not finding any usual way to calculate them.

share|cite|improve this question
What does $3.5.7$ even mean? – filmor Oct 4 '12 at 9:27
@filmor: Those are products. I suspect that this book would represent a common approximation to $\pi$ as $3\cdot1416$. – Brian M. Scott Oct 4 '12 at 10:35
up vote 8 down vote accepted


$$\begin{align*} \frac{1}{2\cdot3}+\frac{1}{4\cdot5}+\frac{1}{6\cdot7} &=\frac{1}{2}-\frac{1}{3}+\frac{1}{4}-\frac{1}{5}+\cdots\\ &=\sum_{n=2}^{\infty}\frac{(-1)^{n}}{n}\\ &=\sum_{n=2}^{\infty}\int_{0}^{-1}x^{n-1}dx\\ &=\int_{0}^{-1}\sum_{n=2}^{\infty}x^{n-1}dx\\ &=\int_{0}^{-1}\frac{x}{1-x}dx\\ &=1-\ln2 \end{align*}$$


$$\begin{align*} \frac{1}{3}+\frac{1}{4}\cdot\frac{1}{2!}+\frac{1}{5}\cdot\frac{1}{3!}+\cdots &=\sum_{n=1}^{\infty}\frac{1}{n+2}\cdot\frac{1}{n!}\\ &=\sum_{n=1}^{\infty}\frac{n+1}{(n+2)!}\\ &=\sum_{n=1}^{\infty}[\frac{1}{(n+1)!}-\frac{1}{(n+2)!}]\\ &=\frac{1}{2} \end{align*}$$

The sum to $m$ terms is

$$\begin{align*} \sum_{n=1}^{m}\frac{1}{n+2}\cdot\frac{1}{n!} &=\sum_{n=1}^{m}\frac{n+1}{(n+2)!}\\ &=\sum_{n=1}^{m}[\frac{1}{(n+1)!}-\frac{1}{(n+2)!}]\\ &=\frac{1}{2}-\frac{1}{(m+2)!} \end{align*}$$

share|cite|improve this answer
$5.7$ is not clear to me still :( – Un Chien Andalou Oct 4 '12 at 12:06
@Flute: Ok, 5.7 seems not very easy to work out as fast as the other two questions. I'll work on it and work it out as soon as possible. – Alfred Chern Oct 4 '12 at 12:17
@Flute: I know how to deal with it now. Please wait. – Alfred Chern Oct 4 '12 at 12:28
I myself has got it $(1+x)^{1/2}$ where $x=1$ is it that? – Un Chien Andalou Oct 4 '12 at 13:31
@Flute: I think it not. How you got it? May be I can check it for you. – Alfred Chern Oct 4 '12 at 14:00

5.6.: Using $\displaystyle\frac1{n\cdot (n+1)} = \frac1n-\frac1{n+1}$: $$\frac12-\frac13+\frac14-\frac15\pm\cdots = 1-\log 2$$ Since $\log(1-x)= -\displaystyle\sum_{n\ge 1}\frac{x^n}n$, convergent at $x=-1$.

5.7.: Perhaps binomial series and generalized binomial coefficients help: $$\begin{pmatrix} -3/2\\n \end{pmatrix} = (-1)^n\cdot \frac{\overbrace{3/2\cdot 5/2\cdot 7/2\cdot..}^n}{n!}$$

5.8.: Observe that $\displaystyle\frac1{n+2}\cdot\frac1{n!} = \frac{n+1}{(n+2)!}$, and try to find a suitable power series..

share|cite|improve this answer

This exercises seems to practise taylor expansions. For the last problem $$e^x = \sum _ { n = 1}^{\infty} \frac{x^n}{ n\mathrm{!}}$$ $$xe^x = \sum _ { n = 1}^{\infty} \frac{x^{n+1}}{ n\mathrm{!}}$$ now you can integrate and take the value at $1$

For the second you look at taylor expansion of $\arccos$ $$ \arccos(x) =\frac{\pi}{2}- \sum _ { n = 1}^{\infty} \frac{1}{4^n} \frac{2n \mathrm{!}}{n\mathrm{!}^2}\frac{1}{2n+1}x^{2n+1}$$ The general term of the second sum is $$ \frac{1 \cdot 3 \dots \cdot (2n+1)}{4^nn\mathrm{!}}=\frac{1 \cdot 3 \dots \cdot (2n)}{4^nn\mathrm{!}}\frac{1}{2^n n\mathrm{!}}=\frac{1}{2^{3n}}\frac{2n\mathrm{!}}{n\mathrm{!} ^2}$$ Now it is not very hard from the taylor expansion to get there.

share|cite|improve this answer
The denominator of the general term of 5.7 is $4^nn!$, not $4n!$. – Brian M. Scott Oct 4 '12 at 11:00
Thank you, edited! – clark Oct 4 '12 at 11:07


$$\begin{align*} 1+\frac{3}{4}+\frac{3\cdot5}{4\cdot8}+\cdots &=1+\sum_{n=1}^{\infty}\frac{3\cdot5\cdots(2n+1)}{4\cdot8\cdots4n}\\ &=1+\sum_{n=1}^{\infty}\frac{3\cdot5\cdots(2n+1)}{2\cdot4\cdots2n}(\frac{\sqrt{2}}{2})^{2n} \end{align*}$$

Set $f(x)=\sum_{n=1}^{\infty}\frac{3\cdot5\cdots(2n-1)}{2\cdot4\cdots2n}x^{2n+1}$, then $1+\frac{3}{4}+\frac{3\cdot5}{4\cdot8}+\cdots=1+f^{\prime}(\frac{\sqrt{2}}{2})$.

$$\begin{align*} f^{\prime}(x)&=\sum_{n=1}^{\infty}\frac{3\cdot5\cdots(2n+1)}{2\cdot4\cdots2n}x^{2n}\\ &=\sum_{n=1}^{\infty}\frac{3\cdot5\cdots(2n-1)\cdot(2n+1)}{2\cdot4\cdots2n}x^{2n}\\ &=\sum_{n=1}^{\infty}\frac{3\cdot5\cdots(2n-1)\cdot2n}{2\cdot4\cdots(2n-2)\cdot2n}x^{2n}+\sum_{n=1}^{\infty}\frac{3\cdot5\cdots(2n-1)}{2\cdot4\cdots2n}x^{2n}\\ &=x^{2}(1+\sum_{n=2}^{\infty}\frac{3\cdot5\cdots(2n-1)}{2\cdot4\cdots(2n-2)}x^{2n-2})+\frac{1}{x}f(x)\\ &=x^{2}(1+f^{\prime}(x))+\frac{1}{x}f(x) \end{align*}$$

Set $g(x)=f(x)+x$, then $g^{\prime}(x)=x^{2}g^{\prime}(x)+\frac{1}{x}g(x)$, by calculation: $$g^{\prime}(x)=\frac{1}{x(1-x^{2})}g(x)$$





as $g^{\prime}(0)=f^{\prime}(0)+1=1$, so $c=1$, $1+\frac{3}{4}+\frac{3\cdot5}{4\cdot8}+\cdots=1+f^{\prime}(\frac{\sqrt{2}}{2})=g^{\prime}(\frac{\sqrt{2}}{2})=2\sqrt{2}$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.